2015
DOI: 10.1016/j.ijpvp.2015.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic evaluation of the microstructure of Grade 91 tubes/pipes

Abstract: a b s t r a c tThis paper assesses the feasibility of transferring a laboratory-based electromagnetic (EM) sensor technique, which has already proved sensitive to significant (e.g. phase balance) or subtle (e.g. number density of fine precipitates) microstructural changes in steel, to non-destructive evaluation of the microstructure of power generation components such as tubes/pipes. It has been found that Grade 91 steels, in different conditions representative of service entry, thermally aged or ex-service, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In this grind-hardening study, it was found that the RMS of the BN signal decreased with increasing hardening depth, as would be expected due to the larger percentage of magnetically hard material in the inspection volume. Similarly, Liu et al (2015) and Wilson et al (2014) were able to successfully distinguish between different heat treatments in grade 91 steel tubes and pipes using BN and coercivity measurements. In this case, the microstructure of the steel, both in terms of the phases present and the precipitate density, influenced the NDT measurement.…”
Section: Barkhausen Noise Inspectionmentioning
confidence: 87%
“…In this grind-hardening study, it was found that the RMS of the BN signal decreased with increasing hardening depth, as would be expected due to the larger percentage of magnetically hard material in the inspection volume. Similarly, Liu et al (2015) and Wilson et al (2014) were able to successfully distinguish between different heat treatments in grade 91 steel tubes and pipes using BN and coercivity measurements. In this case, the microstructure of the steel, both in terms of the phases present and the precipitate density, influenced the NDT measurement.…”
Section: Barkhausen Noise Inspectionmentioning
confidence: 87%
“…Such changes are likely to be long-term, monotonic, and approximately isotropic and may therefore be separable from the influence of at least dynamic loading. It has been suggested in previous literature that it may be possible to use magnetic properties to monitor the microstructural state of engineering components [ 18 – 20 ]. This study has shown that various parameters including stress state, temperature and magnetisation cause significant changes in magnetic permeability and are likely to dominate the subtle influence of microstructural evolution.…”
Section: Discussionmentioning
confidence: 99%
“…A brief introduction to contact thermoelectric power measurements will be given in this section to provide background for the remainder of the study. This introduction is an abbreviated and simplified version of that given in (10). An example experiment will be used in this section to demonstrate the measurement process, introduce the experimental arrangements and generate an example data set; TEP measurements of a 99.5% purity nickel sample are used due to the availability of reference values available in the literature for validation.…”
Section: Background To Thermoelectric Power Measurementsmentioning
confidence: 99%
“…In particular, electromagnetic properties have been seen as particularly promising due to the high sensitivity to numerous microstructural features and the possibility of simple and robust measurement hardware. 2,3 Studies into electrical [4][5][6] as well as a range of magnetic and micromagnetic properties [7][8][9][10] have been conducted. This article will focus on Seebeck coefficient, or 'thermoelectric power' (TEP), as an example, but many of the issues investigated will be common to a range of other properties.…”
Section: Introductionmentioning
confidence: 99%